Ionic effects of NaCl counter osmotic inhibition of germination and seedling growth of Scorzonera hispanica and subsequent plantlet growth is not affected by salt - Dias, L.S. (2015)
Scorzonera (Scorzonera hispanica) is experiencing range reduction in Portugal while its distribution in the Iberian Peninsula largely coincides with areas affected by salinization. Thus two experiments were conducted to evaluate the response of scorzonera to salinity. In the first experiment, seed germination and seedling growth were investigated under osmotic potentials down to −1.21 MPa using NaCl or iso-osmotic polyethylene glycol (PEG) solutions. Results of PEG treatments show that osmotic potential alone reduces germination and seedling growth while on NaCl reductions were much lower. Ionic effects of NaCl are stimulatory and clearly counteract osmotic effects. Most seeds completed germination after being transferred from PEG to distilled water. Conversely, on NaCl recovery results essentially from more time allowed for seeds to complete germination. In the second experiment, young plantlets were treated with NaCl solutions up to 250 mM. In general plantlets were insensitive to NaCl except for a concentration-dependent increase of relative chlorophyll content suggesting that scorzonera tolerance to NaCl might depend upon nitrogen availability. Altogether, results support the conclusion that scorzonera may be a naturally salt tolerant species able to accumulate and sequester NaCl, its tolerance increasing as plants grow older.